Tumour grade significantly correlates with total dysfunction of tumour tissue-infiltrating lymphocytes in renal cell carcinoma - Kawashima, Atsunari (Sci Rep, 2020)
It is important to evaluate the clinical importance of both CD8 T cells and CD4 T cells expression simultaneously because they have crucial networks in tumour targeting immune responses. In 97 RCC patients, RNA sequencing and gene set enrichment analysis of both CD8 and CD4 T cells based on the expression levels of PD-1 and TIM-3 implied that the populations of PD-1+TIM-3+ CD8 T cells and PD-1lowTIM-3 + CD4 T cells were characterized as exhausted CD8 T cells and regulatory CD4 T cells, respectively. These populations of CD4 and CD8 T cells were significantly upregulated in the patients with RCC of higher WHO/ISUP grade (grades 3, 4) (P < 0.001). Moreover, the cytokine productivities of each population in both CD4 and CD8 T cells of the higher-grade patients were significantly lower than those of the lower-grade patients (P < 0.05). Multivariate analysis showed the prognosis of patients with metastatic RCC of higher WHO/ISUP grade treated by nivolumab to be significantly worse than that of patients with lower grade (P = 0.026). This study showed that tumour grade significantly correlated with dysfunction of both CD4+ and CD8+ TILs and the efficacy of nivolumab treatment.